Teachers' Beliefs about the Role of Digital Educational Resources in Educational Practice: A Qualitative Study - Ivan Alberola-Mulet; Marcos Jesús Iglesias-Martínez; Inés Lozano-Cabezas (MDPI AG, 2021)
Information and Communication Technologies and Digital Educational Resources have undergone a rapid evolution and have been swiftly introduced into educational contexts. Teachers play a key role in integrating these technological resources into the classroom. The objective of the present study was to determine the value that teachers attribute to digital resources in their educational practice. Based on a qualitative methodology, the necessary information was obtained via an open-ended interview, in which a Spanish school's Early Childhood and Primary Education teachers participated. The results revealed that teachers value the integration of digital resources into the classroom, though no consensus was reached as to the suitable level of integration. Use satisfaction was mainly related to student motivation. Certain problems or limitations also came to light, however, linked to students' digital training. An important conclusion according to the perception of teachers is that the integration of digital resources in their educational practice was significant and improved the quality of the educational process.